Simulation videos presented in a blended learning platform to improve Australian nursing students' knowledge of family assessment. (July 2018) - Coyne, Elisabeth; Frommolt, Valda; Rands, Hazel; Kain, Victoria; Mitchell, Marion
Abstract: The provision of simulation to enhance learning is becoming common practice as clinical placement becomes harder to secure within Bachelor of Nursing programs. The use of simulation videos within a blended learning platform enables students to view best practice and provides relevant links between theory and practice. Four simulation videos depicting family assessment viewed by a cohort of Australian undergraduate nursing students were evaluated. These videos were professionally developed using actors and experienced family nurses. Surveys were used to explore the students' self-assessed knowledge, confidence and learning preferences before and after exposure to blended learning resources. Students' engagement with the simulated videos was captured via the Learning Management System. Time 1 survey was completed by 163 students and Time 2 by 91 students. There was a significant increase in students' perceived knowledge of family theory Item 1 from a mean 4.13 (SD = 1.04) at Time 1 to 4.74 (SD = 0.89) (Z = −4.54 p < 0.001) at Time 2; Item 2- Knowledge of family assessment improved from mean 3.91 (SD = 1.02) at Time 1 to 4.90 (SD = 0.67) (Z = −7.86 p < 0.001) at Time 2. Also a significant increase in their confidence undertaking family assessment Item 5 from a mean 3.55 (SD = 1.14) at Time 1 to 4.44 (SD = 0.85) (Z = −6.12 p < 0.001) at Time 2. The students watched the videos an average of 1.9 times. The simulated videos as a blended learning resource increases the students' understanding of family assessment and is worth incorporating into future development of courses. Highlights: Simulated patient interaction provides opportunities for students to learn clinical skills. Simulation videos enhance student engagement and learning. Blended learning resources promote flexible student learning. Students prefer interactive learning materials which they can engage with at home and repeatedly. Simulated video resources should be about eight to ten minutes long to support completion of resource and to promote student engagement.